2018
DOI: 10.3389/fonc.2018.00599
|View full text |Cite
|
Sign up to set email alerts
|

CAGE Binds to Beclin1, Regulates Autophagic Flux and CAGE-Derived Peptide Confers Sensitivity to Anti-cancer Drugs in Non-small Cell Lung Cancer Cells

Abstract: The objective of this study was to determine the role of CAGE, a cancer/testis antigen, in resistance of non-small cell lung cancers to anti-cancer drugs. Erlotinib-resistant PC-9 cells (PC-9/ER) with EGFR mutations (ex 19 del + T790M of EGFR), showed higher level of autophagic flux than parental sensitive PC-9 cells. Erlotinib and osimertinib increased autophagic flux and induced the binding of CAGE to Beclin1 in PC-9 cells. The inhibition or induction of autophagy regulated the binding of CAGE to Beclin1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Hence, it is reasonable to conclude that autophagy plays a protective role against OSI-induced CRC suppression. It has been reported that OSI could induce acquired drug resistance in NSCLC patients 40 , mainly due to a second mutation of EGFR (such as C797 mutation) 41 , or activation of by-pass pro-survival signaling pathways such as MET/ERK, HER2, IRE1α or RAS 4144 . Our data demonstrate autophagy as an additional drug resistance mechanism for OSI treatment in both NSCLC and CRC, suggesting that combinatorial use of OSI with autophagy inhibitors may benefit their therapeutic efficacy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is reasonable to conclude that autophagy plays a protective role against OSI-induced CRC suppression. It has been reported that OSI could induce acquired drug resistance in NSCLC patients 40 , mainly due to a second mutation of EGFR (such as C797 mutation) 41 , or activation of by-pass pro-survival signaling pathways such as MET/ERK, HER2, IRE1α or RAS 4144 . Our data demonstrate autophagy as an additional drug resistance mechanism for OSI treatment in both NSCLC and CRC, suggesting that combinatorial use of OSI with autophagy inhibitors may benefit their therapeutic efficacy for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mersakova et al (2018) and Rong et al (2019) have recently shown that CADM1 is a potential biomarker for cervical cancer. There was a significant difference in the promoter Kan et al, 2014;Lai et al, 2014;Kong et al, 2015;Nikolaidis et al, 2015;Xu et al, 2015Xu et al, , 2018Chen et al, 2016;Liou et al, 2016;Huang et al, 2017;Fang et al, Lee et al, 2006;Yeon et al, 2018 methylation of plasma CADM1 and its D-dimer between healthy individuals and those with cervical cancer. Combining these factors to predict metastasis revealed high specificity (90.5%) and sensitivity (80.4%) (Rong et al, 2019).…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 98%
“…Abnormal levels of miRNAs were demonstrated in the process of carcinogenesis or progression, such as lung cancer [ 45 ] and GBM [ 15 , 16 ]. It has been studied that some genes such as miR-373 [ 22 ] or miR-21 [ 21 ] play an important role in above resistance effects of cancer therapy. But there were few studies on whether inhibition on miR-373 may induce above antiresistance effects in GBM treatment and which downstream effector was involved in its process, which need to be confirmed by further experimental data or evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changing the level of above oncogenes or tumor suppressors by using molecular biological methods could provide great assistance to clinical therapy of tumor patients. In addition, some reports showed [ 17 19 ] that the resistance of chemo- or radiotherapy on tumor clinical treatment was also related to the effects of miRNAs, such as miR-100 [ 20 ], miR-21 [ 21 ], miR-373 [ 22 , 23 ], but the underlying mechanism was still unclear.…”
Section: Introductionmentioning
confidence: 99%